Paul, the power of God and the power of “Rome.”: Readings and re-readings from Romans 13.1-7 - Wiese, Werner (Vox Scripturae - Revista Teológica Internacional, 2018)
Paul’s letters in the New Testament are the greatest theological legacy of the “first hand” of the Christian church. In them he faces theological issues that are real puzzles; among them there are texts that seem to conflict with each other. Rom 13.1-7 is one of the most difficult puzzles to be equated. On the one hand, this text is often claimed to support a theory of state according to the will of God; robust subsidies have been seen to legitimize the status quo which, in most cases, favors a small portion of the population and subjects the majority to precarious living conditions. On the other hand, this text is used as material proof of an apostle conniving with the Roman public power and, when compared with other texts of Paul himself, reveals his incoherence and identity divided between different powers and interests; would attest to the apostle’s hybrid biography. The present article addresses some of these questions from several texts of Paul, with greater emphasis on Romans 13.1-7. It concludes with some considerations, emerging of the approaches.